Monitoring community engagement in social learning for sustainability in natural resource management: two Western Australian examples - Thompson, Graham James (Curtin University, 2013)
This thesis examines community engagement in social learning for achieving more sustainable collaborative natural resource management in practice. Results show that while such engagement is being effectively facilitated at the local community level, it is not being scaled-up to the national policymaking level for achieving sustainability in this field in practice. The thesis proposes a tool for monitoring community engagement in social learning to address this problem of community engagement, learning and scale.